Workplace Noise Hazard Education at UD Riwood Sidoarjo - Farikhatul Wasillah; Ratna Ayu Ratriwardhani; Rizka Amirul Sofia; Sindy Nur Fitria; Ongky Putra Abadi; Muslikha Nourma Rhomadhoni (Journal of Health Community Service, 2024)
Noise is a problem that is often found in every industry. The use of machines and tools that support the production process has the potential to cause noise. Noise is the unwanted sound of a business or activity in a certain level and time that can cause disturbances to human health and environmental comfort. UD RiWood is a wood industry in Sidoarjo district that produces goods in the form of pallets. Based on the identification results, there are noise hazards in the production process caused by production equipment. Many workers are not aware of this so that the socialization of noise hazards in the workplace is carried out. Educational activities use the lecture socialization method by delivering noise hazard material, interactive discussions, and providing educational media in the form of posters attached to the workplace area. Practitioners also use the interview method before and after using a test interview instrument (pre-test and post-test). The purpose of this educational activity is to increase workers' knowledge and awareness of the dangers of noise in the workplace. The results of the educational activities that have been carried out show that there is a significant increase in the results of the previous pre-test. The success indicator of these educational activities is the increase in general knowledge about occupational safety and health and related to the dangers of noise in the workplace which is measured by evaluation through a post-test conducted by practitioners.